Evidence for the validity and reliability of the ALS assessment questionnaire: The ALSAQ-40 - Jenkinson, C; Fitzpatrick, R; Brennan, C; Swash, M (2000)
OBJECTIVES: The purpose of the study was to assess the validity and reliability of a new disease specific measure of health-related quality of life for ALS/MND: the 40-item ALS Assessment Questionnaire (ALSAQ-40). DESIGN: We carried out a longitudinal postal survey. The two administrations of the questionnaire were separated by 3 months SAMPLE: Subjects were patients diagnosed with ALS/MND and registered with the UK MND Association. RESULTS: Dimensions of the ALSAQ-40 were shown to have high levels of internal reliability. The ALSAQ-40 was found to be sensitive to changes in self reported overall health state. CONCLUSION: We concluded that the ALSAQ-40 has high levels of reliability and validity and can be used as an outcome measure in studies evaluating new treatment regimes and therapies. (Amyot Lat Scler 1999; 1:33-40) © 1999 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.